Teknologi Tepat Guna UMKM Kotim Kelompok Tani Kecamatan Pulau Hanaut - Puji Santoso; Mustaqiem Mustaqiem (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Appropriate technology is technology that is in accordance with the conditions in which the technology is used and applied both in terms of social, economic, and cultural aspects, so that users can easily participate and can meet their needs effectively and efficiently. Public Transportation of Hanaut Island District is under the auspices of the Forming Alliance Micro, Small and Medium Enterprises (API UMKM), has superior products. As for some products from UMKM, Hanaut Island District, including Sampit Coffee, Virgin Coconut Oil, Coconut Cooking Oil, Lemon Water, Carang Mas and others. In running its business, the Hanaut Island District UMKM in collaboration with local farmers has several obstacles including the slow marketing of UMKM products due to the lack of promotional media and limited marketing areas and also the products of Hanaut Island District UMKM themselves are not well known by the community, causing the product to be slow to sell, Therefore, to overcome the above problems by creating an internet site, the management can arrange up to date promotions according to the type of product and price in the market and can adjust consumer needs. by utilizing information technology can make it easier for consumers to select and order products by looking directly at the type, weight and price of products that suit their needs without having to come to the location